2014
DOI: 10.13044/j.sdewes.2014.02.0004
|View full text |Cite
|
Sign up to set email alerts
|

Solar Distillation System Based on Multiple-Effect Diffusion Type Still

Abstract: The present study intends to develop a high-performance solar-assisted desalination system (SADS) using multi-effect diffusion type still (MEDS) and the vacuum tube solar collector (VTSC). A MEDS prototype was designed and built. The measured result is very close to the estimation. The 10-effect MEDS will produce pure water at about 13.7 L/day/m 2 collector area at a solar irradiation of 600 W/m 2 and 19.7 L/day/m 2 collector area at solar irradiation 800 W/m 2 . For 20-effect still, the yield rate increase is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Together with the increase in blend salt weight, showing an acceptable design parameter for applied solar concentrator. All data was collected when solar intensity was about 300W/m 2 as a selected maximum through winter months in Egypt and not to be compared with weather in Gulf countries and Saudi Arabia [21].…”
Section: Resultsmentioning
confidence: 99%
“…Together with the increase in blend salt weight, showing an acceptable design parameter for applied solar concentrator. All data was collected when solar intensity was about 300W/m 2 as a selected maximum through winter months in Egypt and not to be compared with weather in Gulf countries and Saudi Arabia [21].…”
Section: Resultsmentioning
confidence: 99%
“…An experiment was carried out by Huang et al [19] for a bendedplate MDU, with a wick dimension of 30 cm × 40 cm, using steam as the input. It was found that the measured COP of MDU, R o , as defined in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Chong et al [18,19] designed a similar MEDS of Tanaka et al [15][16][17] but using a bended-plate MDU coupled with a vacuum-tube solar collector. The bended-plate MDU solves the problem of wick peel-off from the heating plate and pure water contamination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, substantial improvement of productivity should be made on solar still for more practical applications. Multi-effect solar still (MES) was developed to overcome this low productivity problem, by recycling wasted latent heat repeatedly [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. As shown in Figure 1, in MES, multiple layers of evaporating wicks and condensing surface are stacked together [14].…”
Section: Desalinationmentioning
confidence: 99%